2023
DOI: 10.1039/d3an01442h
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared fluorescent probe for detecting hydrogen sulfide with high selectivity in cells and ulcerative colitis in mice

Chong-Kang Qin,
Ling Yan,
Zhi-Qing Wang
et al.

Abstract: Although hydrogen sulfide (H2S) is a well-known toxic gas, its vital role as a gas transmitter in various physiological and pathological processes of living systems cannot be ignored. The relevant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…24−28 Although ClO − is one of the vital biomarkers of IBD, fluorescent probes designed to monitor the dynamic ClO − in IBD have been rarely reported so far. 29 To date, a series of fluorescent probes activated by hydrogen sulfide (H 2 S), 30 nitric oxide (NO), 31,32 nitroreductase, 33,34 and intestinal alkaline phosphatase 35 shown that intestinal damage in patients with IBD will lead to the enrichment of inflammatory cells such as macrophages and neutrophils in the intestine, which are involved in regulating the immune response. 36−41 During this process, a large amount of hypochloric acid (HClO) would be produced under the catalysis of myeloperoxidase (MPO) in macrophages and neutrophils, accompanied by high levels of fecal calprotectin and HClO observed in the stool.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−28 Although ClO − is one of the vital biomarkers of IBD, fluorescent probes designed to monitor the dynamic ClO − in IBD have been rarely reported so far. 29 To date, a series of fluorescent probes activated by hydrogen sulfide (H 2 S), 30 nitric oxide (NO), 31,32 nitroreductase, 33,34 and intestinal alkaline phosphatase 35 shown that intestinal damage in patients with IBD will lead to the enrichment of inflammatory cells such as macrophages and neutrophils in the intestine, which are involved in regulating the immune response. 36−41 During this process, a large amount of hypochloric acid (HClO) would be produced under the catalysis of myeloperoxidase (MPO) in macrophages and neutrophils, accompanied by high levels of fecal calprotectin and HClO observed in the stool.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hypochlorite (ClO – ), as one of the most important reactive oxygen species (ROS), can induce mucosal damage, exacerbate inflammatory responses, and accelerate mucosal ulcers in the progress of IBD. Although ClO – is one of the vital biomarkers of IBD, fluorescent probes designed to monitor the dynamic ClO – in IBD have been rarely reported so far . To date, a series of fluorescent probes activated by hydrogen sulfide (H 2 S), nitric oxide (NO), , nitroreductase, , and intestinal alkaline phosphatase has been developed for the detection of IBD. Despite great progress being made, most of these fluorescent probes suffer from low sensitivity, slow response time, and poor uptake by inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Further applications of this probe were used to monitor endogenous upregulation of H 2 S in mouse lungs following LPS injection in models of acute lung injury. Using a similar construct, Li reported 351 (IX-H 2 S), which provided a response at 770 nm with good selectivity over competing ions, metals, amino acids, and thiols 384. This probe was further used to image exogenous and endogenous H 2 S in HCT116 cells, exogenous H 2 S in nude mice, and differences in H 2 S generation in the colon of mouse models of ulcerative colitis.Also in 2014, Xu and Xu reported the doubly protected fluorescein derivative 352, which showed excellent selectivity for H 2 S over Cys, Hcy, NAC, and GSH and was used to image exogenous H 2 S in HeLa cells (Figure…”
mentioning
confidence: 99%